The life works in death: the representation of nature in Blanca Varela’s Luz de día (1963) - Salomón Toledo Navarro, Anfer Enrique (2023)
This study focuses on Blanca Varela’s second collection of poems, Luz de día (1963), where we find a lyricism that consolidates the poetic voice of her first collection of poems through a greater scriptural complexity. The research seeks to approach the representation of nature in his poetry, closely linked to his poetics or ideological-writing praxis. General textual rhetoric is used as the main theoretical framework, with the contributions of Stefano Arduini, Chaïm Perelman, Tomás Albaladejo, and Lakoff and Johnson. The study is divided into three parts: in the first, the rhetorical field of Blanca Varela and the collection of poems is developed; in the second, the poems of the section «Muerte en el jardín» are analyzed from a rhetorical perspective; in the third, the respective conclusions are presented. In overall, the article focuses on the representation of nature in Blanca Varela’s poetry and its relationship with her poetics.